Relationship between the Behavior of Pregnant and Breastfeeding Mothers with Incidence of Stunting in the Public Health Service of Jayapura Regency, Papua Province In 2022 - Tappy, Melkior (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to determine the relationship between the behavior of pregnant and breastfeeding mothers and the incidence of stunting in the Jayapura Regency health service, Papua Province. The type of research used was quantitative by means of a survey and processed descriptively analytically using a cross sectional study approach and analyzed using chi-square. The population in this study was all 2,979 pregnant and breastfeeding mothers. The sample size uses the Slovin formula with a sample result of 99.75 or 100 respondents. Determination of the sample was based on purposive sampling using inclusion and exclusion criteria. The results of research regarding the knowledge of pregnant and breastfeeding mothers showed that out of 100 mothers, 74 (74%) had good knowledge. good attitude 90 (90%), good action 80 (80The results of the relationship test using Chi-Squre on the knowledge and action variables showed p=0.016, which means Ho was rejected. This illustrates that there is a relationship between knowledge and action to prevent stunting in pregnant mother. The results of the relationship between attitudes and actions were found to be p=0.110, which means Ho was accepted. This illustrates that there is no relationship between attitudes and actions to prevent stunting in pregnant mother.